Faktor Penyebab Belum Dilaksanakannya Kode External Causes Pada Berkas Rekam Medis Kasus Kecelakaan Pasien BPJS di Rumah Sakit Umum Daerah Kota Baubau - Wa Ode Sitti Budiaty; Syahrul Ramadhan (Unit Publikasi Ilmiah Perkumpulan Intelektual Madani Indonesia, 2021)
Based on the results of preliminary observations on the medical record file for the BPJS patient accident case that was carried out by researchers at the Baubau City Hospital in 2019, the coding of the diagnosis on the medical record form for the BPJS patient accident case at the Baubau City Hospital was not accompanied by an external cause code. This study aims to identify the causes of the external causes code not yet implemented in the medical record file of BPJS patient accident cases at the Baubau City Regional General Hospital. This research was conducted in the PPTARS room of Baubau City Hospital. The design of this study was a descriptive study with a qualitative approach with a case study design. Research subjects included one inpatient coding officer and head of the medical records field. The object of this research is the medical record file of BPJS patient accident case and the standard operational procedure about external causes in Baubau City Hospital. Data collection techniques was done by observation, interview and documentation study. The results showed that aspects that affected the implementation of the external causes code were Man, Money, and Methods aspects. In the Man aspect, HR has never participated in training related to external causes and there have been no orders from superiors / centers regarding external causes data needs. In the Money aspect, the patient's external causes code has not had a significant effect on the patient's INA-CBGs claim and for the Methods aspect, there is no SOP related to external causes. For this reason, officers should be given training, external causes codes are taken into account in making INA-CBGs claim reporting and RL4a reports related to morbidity, and SPOs about coding external causes are compiled and applied